The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12225-013-9474-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapania multiflora, a distinctive new species of Cyperaceae (Mapanioideae) from Borneo

Abstract: Summary. Mapania multiflora is described and illustrated. It is vegetatively similar to taxa with broad leaves and pseudopetioles, such as M. cuspidata. However, it is reproductively similar to sect. Thoractostachyum with a paniculate inflorescence and furrowed fruit. The DNA is similar to M. bancana in sect. Thoractostachyum, in the three sampled cpDNA regions: atpH-F, trnL-F and psbA-trnH. However, it is identical to none of these due to its unique combination of vegetative, reproductive and molecular charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The studies of genus Mapania in Borneo and particularly Sarawak has been neglected since the last enumeration by Simpson (1992) until Shabdin et al (2013aShabdin et al ( & 2013b added two new species and another three recently, with one new record (Miraadila & Shabdin, 2016) to the list making it 31 species in total. In attaining the important knowledge of this valuable genus, a comprehensive research has been conducted to study the delimitation of the genus in Sarawak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of genus Mapania in Borneo and particularly Sarawak has been neglected since the last enumeration by Simpson (1992) until Shabdin et al (2013aShabdin et al ( & 2013b added two new species and another three recently, with one new record (Miraadila & Shabdin, 2016) to the list making it 31 species in total. In attaining the important knowledge of this valuable genus, a comprehensive research has been conducted to study the delimitation of the genus in Sarawak.…”
Section: Resultsmentioning
confidence: 99%
“…The number however has increased as several new species been discovered recently, particularly from Malesian region i.e. Shabdin et al (2013aShabdin et al ( & 2013b, and Miraadila and Shabdin (2016). Mapania section Pandanophyllum is endemic to Asia, Indomalesia, Australia and the Pacific Islands.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of Mapania species in Sarawak is tremendous, with 31 out of 71 world's total number are recorded includes three newly described species; M. sapuaniana Shabdin (2013a); M. multiflora Shabdin (2013b), M. meekiongii and M. kadimiana Shabdin, Meekiong & Miraadila (Shabdin et al, 2016). Our recent field excursions collected many interesting specimens that morphologically not matching with the existing species recorded for Sarawak.…”
Section: Introductionmentioning
confidence: 95%
“…This family currently includes two subfamilies, Mapanioideae and Cyperoideae (Govaerts et al, 2007;Muasya et al, 2009), with genus Mapania being under subfamily Mapanioideae. The diversity of Mapania species from Sarawak is tremendous, with 31 out of 71 world's total number are recorded (Miraadila et al, 2016). Studies on Mapania of Sarawak since 2008 by Shabdin et al (2013aShabdin et al ( , 2013bShabdin et al ( , 2016 has observed the high tendency of endemicity of the species to Borneo (M. longiflora, M. angustifolia, M. lorea, M. debilis, M. maschalina, M. obscuriflora, M. richardsii, M. borneensis, M. latifolia and M. hispida), and hyper-endemicity (M. foxworthyi, M. graminea, M. sapuaniana and M. multiflora).…”
Section: Introductionmentioning
confidence: 99%
“…M. sapuaniana for example, has so far only been recorded in a small area at Sungai Joh (approx. 3 km radius) of Lanjak Entimau Wildlife Sanctuary (LEWS) (Shabdin et al, 2016), while M. ballehensis, M. kipas and M. mirae are recorded only from Baleh National Park. In many field expeditions conducted since 2008, the effort of collecting living specimens to be planted in our arboretum has failed, although the collection includes preserving some soil of the species original habitat.…”
Section: Introductionmentioning
confidence: 99%